Recognition and management of auditory verbal hallucinations in borderline personality disorder - M. B. A. Niemantsverdriet; M. B. A. Niemantsverdriet; C. W. Slotema; C. W. Slotema; I. H. A. Franken; J. Brandsma; M. J. P. M. Verbraak; M. L. Deen; J. D. Blom; J. D. Blom; J. D. Blom; M. Van der Gaag (Frontiers in Psychiatry)
BackgroundAuditory verbal hallucinations (AVH) are experienced by 25% of all people diagnosed with a borderline personality disorder. Since the impact of these hallucinations is often substantial, we asked ourselves how often they are discussed in clinical practice, whether they are treated, and if so, how and to what effect.MethodsWe studied the clinical files of 130 people under treatment at a specialized outpatient clinic for people with personality disorders, and compared the data on the presence and treatment of AVH to those collected in four prior scientific studies by our group.ResultsOf the 130 participants to those earlier studies, 42 had reported on experiencing AVH ≥ once per week. In 31% of the cases this had been missed by the treating healthcare professionals. Of the people suffering from severe AVH, a concurrent schizophrenia spectrum disorder was diagnosed in only 10%. A minority of 41% had received targeted treatment for their AVH. Doses of antipsychotics had been relatively low compared to those recommended for psychotic disorders, and yet all patients treated had reported a decrease in the frequency or severity (or both) of their AVH. Unfortunately, 93% also reported side effects, which led 57% of the group to discontinue this type of treatment. Nonpharmacological treatments such as cognitive behavioral therapy had been offered only to a minority of the participants.ConclusionEven in specialized clinical settings it remains challenging to establish the possible presence of AVH in people with a borderline personality disorder. And yet this is worth the effort because of the impact that these hallucinations tend to have, and the positive effects of antipsychotic treatment here presented. Further research is needed to develop algorithms to optimize doses in individual patients, to develop treatment guidelines, and to explore the effects of nonpharmacological treatments.